PEMANFAATAN VIRTUAL LAB PENDETEKSI GERAK BERBASIS ESP32 DAN MICROPYTHON PADA MATA KULIAH SISTEM OTOMASI - Kadek Mei Pramana; Nyoman Santiyadnya; I Komang Gede Sukawijana (Jurnal Pendidikan Teknik Elektro Undiksha, 2026)
The implementation of microcontroller practicum learning in Automation Systems courses often faces challenges in the form of limited hardware quantities in the laboratory, high component procurement costs, and the risk of equipment damage due to wiring errors by students. This study aims to develop and test the effectiveness of a virtual laboratory for an ESP32 and MicroPython-based motion detection system by utilizing the Wokwi simulation platform as an alternative interactive learning medium. The research method applied is Research and Development (R&D) with a three-stage model, including planning, production, and evaluation. Functional testing of the circuit is carried out using the black-box testing method, while the level of media effectiveness is measured through a trial implementation in the classroom using a student response questionnaire. The results of the functional testing indicate that the motion detection system is able to read changes in conditions in real-time with a stable response through HIGH and LOW logic transitions. Furthermore, the results of the student response questionnaire analysis show an average percentage of effectiveness of 88.75%, which places this virtual laboratory in the Very Effective category. This media has proven to be very superior in facilitating time efficiency and experimental safety (95%) as well as increasing learning independence (90%), so it is suitable for application as an efficient and economical interactive practical tool.